2015
DOI: 10.3389/fmicb.2015.01078
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure adaptation of a sulfate reducer from the deep subsurface

Abstract: Microbial life in deep marine subsurface faces increasing temperatures and hydrostatic pressure with depth. In this study, we have examined growth characteristics and temperature-related adaptation of the Desulfovibrio indonesiensis strain P23 to the in situ pressure of 30 MPa. The strain originates from the deep subsurface of the eastern flank of the Juan de Fuca Ridge (IODP Site U1301). The organism was isolated at 20°C and atmospheric pressure from ~61°C-warm sediments approximately 5 m above the sediment–b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 95 publications
(126 reference statements)
0
22
0
Order By: Relevance
“…Increasing pressure affects e.g., motility, cell division, DNA replication, transcription, translation, or certain enzymatic reactions (Marietou and Bartlett, 2014 ) and increasing temperature has recently been shown to increase damage of cell walls and DNA by protein racemization and DNA depurination reactions (Lever et al, 2015 ). In a recent study, sulfate reducers isolated from deep and hot (~60°C, 30 MPa) sediments at the Juan de Fuca Ridge showed adaptation to the increased pressure and temperature e.g., by exchanged membrane lipid composition and an increase of their optimum growth temperature (Fichtel et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing pressure affects e.g., motility, cell division, DNA replication, transcription, translation, or certain enzymatic reactions (Marietou and Bartlett, 2014 ) and increasing temperature has recently been shown to increase damage of cell walls and DNA by protein racemization and DNA depurination reactions (Lever et al, 2015 ). In a recent study, sulfate reducers isolated from deep and hot (~60°C, 30 MPa) sediments at the Juan de Fuca Ridge showed adaptation to the increased pressure and temperature e.g., by exchanged membrane lipid composition and an increase of their optimum growth temperature (Fichtel et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fichtel et al. (, ) investigated a microbial community residing above a ridge flank SBI with known sulfate diffusion. They suggested that 30–40 m of hemipelagic clay overlying the basement could act as a hydrogeological barrier for advective fluid flow, and therefore, stop the transportation of particles such as microbial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Desulfovibrionales have been cultured from a variety of subsurface environments (e.g., Magot, Basso, Tardy‐Jacquenod, & Caumette, ; Pedersen, Arlinger, Ekendahl, & Hallbeck, ; Sass & Cypionka, ) with in situ temperatures >60°C (Bale et al., ; Fichtel et al., ), exceeding their optimum growth temperature of ~40°C. Cores 322‐C0012A‐29R to 322‐C0012A‐56R (313 mbsf–554 mbsf) were obtained from depths with in situ temperatures of 40–63°C (Henry et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we do not yet know the in situ microbial survival mechanisms in the subsurface and how they have been/were affected by the prevailing geologic and environmental conditions. It is also difficult to establish whether the microbes detected in the deep subsurface represent environmental conditions at the time of deposition or if they reflect changes that took place after deposition (Fredrickson et al, 1995b;1997;Fichtel et al, 2015;Inagaki et al, 2015). This is further complicated by the fact that drilling and fracturing fluids used during development, introduces large quantities of labile carbon, nutrients, and exogenous organisms into the subsurface Lester et al, 2015;Gaspar et al, 2014;) making it unclear whether indigenous communities exist in these shale formations.…”
Section: Introductionmentioning
confidence: 99%